Fitness & Sports Medicine - Seitz H; Preissler E; Catalá-Lehnen P; Weitl M (Deutsche Zeitschrift für Sportmedizin)
Background and Objectives: A variety of training methods has developed within hypoxic training. The continuous live low-train high method offers simple usability, but effects on endurance capacity are still almost empirically unproven. To clarify whether the continuous live low-train high method has positive effects on the body, it seems worthwhile to collectexploratively the most frequently studied variables and analyzethem for similarities.Methods: A systematic review was conducted to examine the literature onthe continuous live low-train high method for the most frequently-tested variables of endurance capacity. Studies which examined continuous endurance training in normobaric hypoxia from the earliest records up to June 2019 were included.Results: Twelve studies met the criteria and were analyzed. Oxygen uptake at the second ventilatory threshold tested in normoxia exhibits significant changes in six studies through hypoxic training, whereas the changes due to normoxic training are mostly non-significant. The remaining ventilatory, hematological and performance-related variables show only partially significant changes and cannot demonstrate differences between hypoxic and normoxic training.Discussion: The consideration of the variables revealed similarities in the oxygen uptake at the second ventilatory threshold, but a clear detection of differences between hypoxic continuous live low-train high and normoxic training was not possible. This review offers an overview of already-examined variables and recommends additional consideration of submaximal variables of endurance capacity in study designs.KEY WORDS: Altitude, Hypoxia, Hypoxic Training, Continuous , Cardiopulmonary